2012
DOI: 10.1097/mao.0b013e3182487fee
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Vestibular Nerve Schwannomas

Abstract: This exploratory study brings new hypotheses to be tested and thus works toward clarifying the causes and mechanisms involved in the cause and development of vestibular nerve schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The study by Schoemaker, et al 14 found that the risk of acoustic neuroma was not significantly reduced in participants who had a history of head trauma (OR=0.8, 95% CI: 0.6–1.1). The result was consistent with the case-control study by Corona, et al 18 (OR=1.37, 95% CI: 0.66–2.82) and the cohort study by Inskip, et al 37 (RR=0.8, 95% CI: 0.4–1.7). However, one neighborhood-base case-control study indicated a two-fold increase in acoustic neuroma risk in men 30 years or older after a major head trauma.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study by Schoemaker, et al 14 found that the risk of acoustic neuroma was not significantly reduced in participants who had a history of head trauma (OR=0.8, 95% CI: 0.6–1.1). The result was consistent with the case-control study by Corona, et al 18 (OR=1.37, 95% CI: 0.66–2.82) and the cohort study by Inskip, et al 37 (RR=0.8, 95% CI: 0.4–1.7). However, one neighborhood-base case-control study indicated a two-fold increase in acoustic neuroma risk in men 30 years or older after a major head trauma.…”
Section: Discussionsupporting
confidence: 91%
“…After searching PubMed and the bibliographies of all identified relevant publications, as well as screening by the inclusion and exclusion criteria, 11 case-control studies were eligible. 11 12 13 14 15 16 17 18 19 20 21 The study authors, publication year, study site, sample size (numbers of case patients and control subjects), type of control, research instruments, and research contents are all listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the German part of Interphone, medical ionising radiation gave OR = 0.97, 95% CI=0.54–1.75 for acoustic neuroma ( 19 ) . In a study from Brazil on 44 acoustic neuroma patients and 104 controls, exposure to >1 cranial X-ray investigation gave OR = 4.55; 95% CI = 1.10–19.2 ( 20 ) . …”
Section: Discussionmentioning
confidence: 99%
“…Most [4][5][6][7], but not all [8], studies examining the association between self-reported occupational noise exposure and VS have found a direct association. In contrast, two studies estimating occupational noise exposure via a job exposure matrix did not find an association [3,9].…”
Section: Introductionmentioning
confidence: 99%